Assessing Damage to Beam–Column Connections in Reinforced Concrete Structures from Vibrational Measurement Results. Issue 3 (3rd July 2019) - Sentosa, Bastian-Okto-Bangkit; Bui, Quoc-Bao; Ple, Olivier; Plassiard, Jean-Patrick; Perrotin, Pascal
Abstract: At present, dynamic measurements enable the diagnosis of an existing structure at a global scale (the whole structure), while the identification and assessment of local damage (at each element of the structure) remain to be explored. In this study, diagnosis at a local scale was experimentally investigated on a reinforced concrete (RC) frame structure consisting of two columns and one beam. The RC frame was loaded in several stages and dynamic measurements were recorded at each unloading stage using accelerometers. The experimental results were first presented: the appearance of damage, the evolution of natural frequencies and the stiffness changes. Then, a technique of damage characterization was applied which takes into account the semi-rigid connections of the frame. The stiffness of the connections was identified by calibrating the numerical dynamic responses with those obtained from the experiment. Fixity factors were introduced to assess the stiffness changes in the semi-rigid connections. The validity of the identified fixity factors was evaluated using the static experimental results. This study showed that the results from dynamic measurements coupled with a simple finite element model could provide a rapid and effective method to assess the damage evolution of RC frame structures.